2021
DOI: 10.1177/00472875211037745
|View full text |Cite
|
Sign up to set email alerts
|

Examining Tourism Consumers’ Attitudes and the Role of Sensory Information in Virtual Reality Experiences of a Tourist Destination

Abstract: The purpose of this research is twofold: firstly, we aim to understand the role of virtual reality (VR) in influencing tourism consumers’ attitudes toward a tourist destination and, secondly, understand the influence of different levels of sensory information presented through VR experiences on the development of mental imagery, attitudes toward the destination, and visit intention. We tackle this through a multistudy experimental approach. First, in study 1, we demonstrate that VR plays a positive role in enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 79 publications
2
54
2
4
Order By: Relevance
“…The perception of presence is likely to elicit emotions, such as happiness and enjoyment, through VR immersion. Alyahya and McLean [38] claimed that VR can advance the sense of presence, and the sense of existence is a psychological state of feeling completely immersed in the virtual world and a feeling of "being there" in the computer-mediated environment. The cognitive processing of mental images can stimulate a high level of presence in the context of a high sensory VR experience.…”
Section: Sense Of Presence and Its Moderating Rolementioning
confidence: 99%
See 2 more Smart Citations
“…The perception of presence is likely to elicit emotions, such as happiness and enjoyment, through VR immersion. Alyahya and McLean [38] claimed that VR can advance the sense of presence, and the sense of existence is a psychological state of feeling completely immersed in the virtual world and a feeling of "being there" in the computer-mediated environment. The cognitive processing of mental images can stimulate a high level of presence in the context of a high sensory VR experience.…”
Section: Sense Of Presence and Its Moderating Rolementioning
confidence: 99%
“…Previous investigations on virtual tourism mostly focused on tour experience [40], destination attitude, and travel intention [38,66,67] and only slightly discussed the relationship between presence and destination image. A few studies, such as that of Hyun and O'Keefe [71], found the correlation between telepresence and cognitive and conative images.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After external stimuli are input into the body of tourists through the senses, the tourists still need to go through a complex psychological process before they can have a conscious sensory experience, affecting subsequent behavioral choices ( Jiang, 2020 ). Some scholars have proposed the “emotion-cognitive dual system model” to subdivide the complex psychological state of individuals ( Alyahya and McLean, 2021 ). The dual system theory is also regarded as an information processing theory, which explains the formation of individual attitude preferences through two different information processing pathways (the limbic pathway of the emotional system and the central pathway of the cognitive system; Alyahya and McLean, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Some scholars have proposed the “emotion-cognitive dual system model” to subdivide the complex psychological state of individuals ( Alyahya and McLean, 2021 ). The dual system theory is also regarded as an information processing theory, which explains the formation of individual attitude preferences through two different information processing pathways (the limbic pathway of the emotional system and the central pathway of the cognitive system; Alyahya and McLean, 2021 ). Among them, the emotional system adopts the principle of intuition, requiring individuals to process information quickly with less effort.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%